Iran’s Nuclear Decision Making and the Issue of Nuclear Non-Proliferation in the International System - Suleiman, Ibrahim; Mohammed, Hamza Shehu; Haruna, Haruna Mohammed (American International Journal of Social Science Research, 2018)
This paper studies the reason for Iran’s nuclear decisions making by using the realist approach in the international politics, also the issue of nuclear non-proliferation in the international system and why the international system is totally against the Iran’s nuclear program? The study employs both primary and secondary sources as a method of data collection. The study reveals that that national interest should come first before any collective ones. The process which decisions are made is only determined by self-serving interests of those who possess power in the international system. The realist school of thought provides the critical opinions propounded by various political science scholars on power politics and national interest in the international system. According to Hans Morgenthau a classical realist scholar, society has to be governed generally by objective laws which are rooted in human nature. To him theory is necessary so that to bring order in the international politics, he rejected the idea of liberalism and idealism. Theory has to reflect the objective laws like power, military, diplomacy and norms of the society. First of all we have to look at the human nature which is seen as a rational, we have to examine through individual, group, and societal level because naturally human nature is selfish. Morgenthau defined the state as a collection of human beings who are self-interested, thus the state will have to deal with order interested states in the world politics. The aim of state in the international politics is pursuing national interest which is basically about power. He viewed international politics as a struggle for power.Thus, the realist scholars maintained that in the international politics, states happened to be the key actors and that politics is a conflictual, a struggle for anarchical environment in which nation-states defend on their own capabilities to survive.